An Shen Ding Zhi Ling Alleviates Symptoms of Attention Deficit Hyperactivity Disorder via Anti-Inflammatory Effects in Spontaneous Hypertensive Rats - Song, Yuchen; Yuan, Haixia; Chen, Tianyi; Lu, Manqi; Lei, Shuang; Han, Xinmin (Frontiers in Pharmacology, 2021)
Attention deficit hyperactivity disorder (ADHD) is a childhood onset chronic neurobehavioral disorder, with multiple genetic and environmental risk factors. Chronic inflammation may be critical for the progression of ADHD. An Shen Ding Zhi Ling (ASDZL) decoction, a traditional Chinese medicine prescription, is clinically used in ADHD treatment. In this study, we investigated the effects and underlying anti-inflammatory mechanisms of ASDZL in young spontaneously hypertensive rats (SHRs), a widely used model of ADHD. SHRs were divided into the SHR model group (vehicle), atomoxetine group (4.56 mg/kg/day) and ASDZL group (21.25 g/kg/day), and orally administered for four weeks. Wistar Kyoto rats were used as controls (vehicle). We found that ASDZL significantly controlled hyperactivity and impulsivity, and improved spatial memory of SHRs in the open field test and Morris water maze test. ASDZL reduced the pro-inflammatory factors interleukin (IL)-1β, IL-4, IL-6, tumor necrosis factor (TNF)-α and monocyte chemoattractant protein (MCP)-1 and increased anti-inflammatory factor IL-10 in SHRs, and decreased the activation of microglia, astrocytes and mast cells in the prefrontal cortex (PFC) and hippocampus. Furthermore, the results indicated that ASDZL inhibited the neuroinflammatory response by protecting the integrity of the blood-brain barrier and suppressing the mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB signaling pathways of SHRs. In conclusion, these findings revealed that ASDZL attenuated ADHD symptoms in SHRs by reducing neuroinflammation.